PENGARUH SOCIAL MEDIA MARKETING, BRAND AWARENESS DAN LOKASI TERHADAP KEPUTUSAN PENGGUNAAN LAYANAN DI SWISS-BELHOTEL TUBAN - Ni Luh Santi Ayuni; I Nengah Suardhika; I Gde Yudhi Hendrawan (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
The function of the hotel was only as a place to stay for tourists who went on business trips or vacations. But over time, the function of the hotel has increased. Currently, hotels have other functions than as temporary residences for tourists, but can also be used for weddings, corporate meetings, new product launches. With the changes in the hotel's function, entrepreneurs who are engaged in the hotel business can compete to survive in the competition. One hotel that is experiencing quite competitive competition is the Swiss-belhotel Tuban. This can be seen during the period 2016-2020 room sales fluctuated. Therefore, with the competition so competitive, effective marketing activity is needed for Swiss-belhotel Tuban so that consumers are willing to decide to use the services at Swiss-belhotel Tuban. Therefore, the researcher aims to determine the effect of social media marketing, brand awareness, and location on the decision to use services at Swiss-belhotel Tuban. This research was conducted at Swiss-belhotel Tuban. The method of data collection was through distributing questionnaires to 100 respondents who were guests who had stayed at Swiss-belhotel Tuban. The sampling technique used is non-probability sampling using accidental sampling, which is sampling by chance. This means any member of the population who happens to be met by the researcher at the time of the study, that member is used as a sample. The data analysis technique in this study used multiple linear analysis techniques which were processed using the IBM SPSS 23.0 for Windows application. The results of the analysis show that 1) Social media marketing has a positive and significant effect on service use decisions at Swiss-belhotel Tuban. 2) Brand awareness has a positive and significant effect on service use decisions at Swiss- belhotel Tuban. 3). The location has a positive and significant effect on the decision to use services at Swiss-belhotel Tuban.